2016
DOI: 10.1016/j.vaccine.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Equity in disease prevention: Vaccines for the older adults – a national workshop, Australia 2014

Abstract: On the 20th June, 2014 the National Health and Medical Research Council's Centre for Research Excellence in Population Health "Immunisation in under Studied and Special Risk Populations", in collaboration with the Public Health Association of Australia, hosted a workshop "Equity in disease prevention: vaccines for the older adults". The workshop featured international and national speakers on ageing and vaccinology. The workshop was attended by health service providers, stakeholders in immunisation, ageing, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Despite influenza vaccine being recommended in many countries for patients with CVD [22], it has not made its way into practice as a routine measure to protect patients at risk, with vaccination rates in patients with CVD being low [23]. It has been shown that clinicians in general have a low awareness of adult vaccination and are not strong advocates for vaccination in adults [24,25]. Improved clinician awareness of the benefits of influenza vaccine in prevention of CVD events is needed to take advantage of vaccination as low-hanging fruit for prevention of AMI.…”
Section: Resultsmentioning
confidence: 99%
“…Despite influenza vaccine being recommended in many countries for patients with CVD [22], it has not made its way into practice as a routine measure to protect patients at risk, with vaccination rates in patients with CVD being low [23]. It has been shown that clinicians in general have a low awareness of adult vaccination and are not strong advocates for vaccination in adults [24,25]. Improved clinician awareness of the benefits of influenza vaccine in prevention of CVD events is needed to take advantage of vaccination as low-hanging fruit for prevention of AMI.…”
Section: Resultsmentioning
confidence: 99%
“…This limited the accessibility of vaccination by the RCP for employees working exclusively on weekends, evening shifts and part‐time on days where the RCP was not present. Further, the timing of influenza vaccination is recommended to commence in March and April prior to peak influenza season starting from June . The RCP did not commence employment until late April, limiting opportunities for providing employee education and promotion of the service to overcome perceived lack of vaccine efficacy or necessity as a barrier to uptake .…”
Section: Discussionmentioning
confidence: 99%
“…Influenza is the leading cause of vaccine‐preventable death and hospitalisations due to notifiable communicable disease in Australia . Older adults living in residential aged care homes (RACHs) are particularly susceptible to influenza‐associated morbidity and mortality due to increased frailty, the presence of multiple chronic medical conditions and impaired response to antiviral drug therapy . The annual number of influenza‐related deaths in Australia was the highest recorded in 2017, with 91% of influenza‐related deaths recorded in people aged over 65 years .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid testing and a discussion about lifestyle during consultations are both used to identify risk which is the basis for prescribing cholesterol-lowering medicines which have as their goal a reduced risk of future cardiac disease. A great deal of effort is expended on interventions such as statins or smoking cessation despite observations suggesting that these have significantly less preventative efficacy against cardiac diseases than influenza vaccination [11,[33][34][35]65]. Inexplicably, despite the evidence that influenza vaccination can reduce the risk of cardiac disease [11,[33][34][35], it is not typically prescribed for adults <65 years until after a cardiac event.…”
Section: Integrating Vaccination Into a P4 Medicine Strategymentioning
confidence: 99%